The Cervicovaginal Microbiota and Its Associations With Human Papillomavirus Detection in HIV-Infected and HIV-Uninfected Women. (11th August 2016) - Reimers, Laura L.; Mehta, Supriya D.; Massad, L. Stewart; Burk, Robert D.; Xie, Xianhong; Ravel, Jacques; Cohen, Mardge H.; Palefsky, Joel M.; Weber, Kathleen M.; Xue, Xiaonan; Anastos, Kathryn; Minkoff, Howard; et al.
Abstract: Background. Bacterial vaginosis (BV) is characterized by low abundance of Lactobacillus species, high pH, and immune cell infiltration and has been associated with an increased risk of human papillomavirus (HPV) infection. We molecularly assessed the cervicovaginal microbiota over time in human immunodeficiency virus (HIV)–infected and HIV-uninfected women to more comprehensively study the HPV-microbiota relationship, controlling for immune status. Methods. 16S ribosomal RNA gene amplicon pyrosequencing and HPV DNA testing were conducted annually in serial cervicovaginal lavage specimens obtained over 8–10 years from African American women from Chicago, of whom 22 were HIV uninfected, 22 were HIV infected with a stable CD4 + T-cell count of > 500 cells/mm 3, and 20 were HIV infected with progressive immunosuppression. Vaginal pH was serially measured. Results. The relative abundances of Lactobacillus crispatus and other Lactobacillus species were inversely associated with vaginal pH (all P < .001). High (vs low) L. crispatus relative abundance was associated with decreased HPV detection (odds ratio, 0.48; 95% confidence interval, .24–.96; P trend = .03) after adjustment for repeated observation and multiple covariates, including pH and study group. However, there were no associations between HPV and the relative abundance of Lactobacillus species as a group, nor with Lactobacillus gasseri, Lactobacillus iners, and Lactobacillus jensenii individually. Conclusions. L. crispatus may have a beneficial effect on the burden of HPV in both HIV-infected and HIV-uninfected women (independent of pH).